Ice-Flow Dynamics During the Final Stage of the Fraser Glaciation (MIS2) in the Fraser Lowland, BC, Canada - Raphael Gromig; Kenya Franz; Brent Ward; John J. Clague (Quaternary)
Although the Late Pleistocene glaciation history of the Fraser Lowland (BC, Canada) is relatively well studied, little is known about ice-flow directions during the last glaciation (Fraser glaciation). Lidar imagery from the western Fraser Lowland was used to identify and interpret previously unrecognized glacial landforms in a heavily urbanized and vegetated area. This indicates patterns of ice flow during the latest stage of the Fraser glaciation (Vashon stade) of the Cordilleran Ice Sheet. The imagery provides a picture of dominant SSE flow from the Strait of Georgia in the western part of the study area, and SSW flow from the southern Coast Mountain valleys in the eastern part, resulting in an overall southward flow, as documented in the uplands in the southern part of our study area. No evidence for a substantially different ice flow could be identified. Three new radiocarbon ages from the Sechelt area ca. 40 km northwest of the Fraser Lowland indicate a proximal ice margin in the Strait of Georgia already ca. 30 cal ka BP, well before the Coquitlam ice advance in the Fraser Lowland. These ages contribute to the unsolved discussion if this ice margin advanced onto the Fraser Lowland, yet further studies are needed.